Implementasi literasi budaya dan kewargaan sebagai solusi disinformasi pada generasi millennial di Indonesia - Anggi Pratiwi; Eflinnida Nurul Komaril Asyarotin (Jurnal Kajian Informasi dan Perpustakaan, 2019)
The emergence of disinformation phenomena that occur currently in the millennial generation is due to the easy-going attitude that believes in the information obtained without looking at the truth or examining the credibility of the information source. Eventually, the millennial generation does not have the analytical thinking process of using information. The purpose of this study was to get a picture of disinformation that occurred in the millennial generation and explained the application of cultural literacy and citizenship as a solution to overcome disinformation. The research used the literature study method with a qualitative approach. Data collection used primary and secondary data obtained through various kinds of literature in the last ten years (2009-2019) such as books, e-books, e-journals, and proceedings. Based on the results of the analysis of the problems studied and supported by the theory used, the results showed that cultural and citizenship education could be applied in millennial generation literacy styles. This generation could be more selective in receiving and processing information obtained, could prevent the emergence of hoaxes and hate speech circulating in the community and instill cultural values and citizenship in the lifestyle in the millennial era. The steps taken are activity programs that contain useful information processing process that shapes an individual to become more selective in processing information obtained as well as implementing cultural literacy and citizenship independently in schools, family, and environment.